2017
DOI: 10.1177/0748233717718974
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the endocrine-disrupting effects of homosalate (HMS) and 2-ethylhexyl 4-dimethylaminobenzoate (OD-PABA) in rat pups during the prenatal, lactation, and early postnatal periods

Abstract: Homosalate (HMS) and 2-ethylhexyl 4-dimethylaminobenzoate (OD-PABA) are ultraviolet filters. We aimed to investigate the effects of dermal exposure to HMS and OD-PABA during the prenatal, lactation, and early infancy periods on pubertal development and thyroid function in male and female rats. The thyroid glands, uteri, testes, prostate glands, and seminal vesicles were excised and weighed, the reproductive organs were analyzed histologically, and the serum hormone levels were measured. In the prenatal period,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…According to a report by Erol et al . (6), dermal exposure to OD-PABA did not affect pubertal development or thyroid function in female or male rats. As such, OD-PABA was not classified as an endocrine disrupting chemical.…”
Section: Hazard Identificationmentioning
confidence: 85%
“…According to a report by Erol et al . (6), dermal exposure to OD-PABA did not affect pubertal development or thyroid function in female or male rats. As such, OD-PABA was not classified as an endocrine disrupting chemical.…”
Section: Hazard Identificationmentioning
confidence: 85%
“…Both octisalate and homosalate are water insoluble that leads to their high substantivity, which is the ability to retain its effectiveness after exposure to water and perspiration [72]. HMS does not have endocrine disruptor effects on thyroid function and the pubertal development of female and male rats [73]. Another study says HMS is a potential endocrine disruptor and studies in cells suggest it may impact hormones.…”
Section: Homosalatementioning
confidence: 99%
“…Both octisalate and homosalate are water insoluble that leads to their high substantivity, which is the ability to retain its effectiveness after exposure to water and perspiration [110]. HMS does not have endocrine disruptor effects on thyroid function and the pubertal development of female and male rats [111]. Another study says HMS is a potential endocrine disruptor and studies in cells suggest it may impact hormones.…”
Section: Homosalatementioning
confidence: 99%
“…In 2018, the EWG reported that a large increase in these inorganic ilters with ~41% of sunscreens in the United States designated as mineral only. This igure has more than doubled (from 17%) since 2007 [111] [63]. Only two sunscreen active ingredients approved in the US, avobenzone (butylmethoxydibenzoylmethane) and zinc When corals absorb these chemicals, they have a similar reaction as they would if surrounding water temperatures were to get too warm.…”
Section: Sunscreen Formulationmentioning
confidence: 99%